Metodologia para a análise dos efeitos da geração distribuída sobre as características operacionais dos sistemas de distribuição utilizando técnicas multicriteriais - Barin, Alexandre (2007)
Nowadays, the Brazilian electric systems need the development of new researches and tools, in order to obtain a logic solution to maintain and improve the reliability and the quality of the power delivered to customers. Therefore, the study of the appropriate connection of distributed generation sources is an essential topic to be analyzed, since this process may provide positive impacts along the feeders. An appropriate DG site is an important aspect mentioned in the PRODIST (Proceedings of Electric Energy Distribution on Electrical National System), inside section 3. For now, the PRODIST is just an orientating tool established by the ANEEL - National Regulatory Agency of Electric Energy. It is important to observe that after the approval of PRODIST, this tool will be the standard for several processes considering planning and operation of distribution systems in Brazil. During the development of this work the main types of distributed energy sources were presented in order to observe their characteristics and their applications on distributions networks. Besides, the main effects of the DG operation inside three distribution system models were analyzed through the software DigSilent®, considering power losses and voltage levels. Moreover, this study intends to perform a multi-objective analysis defining some quantitative and qualitative parameters evaluated by specific softwares, according to the types of parameters. It is important to emphasize that the appropriate choice of these parameters is essential to support the final results, since a wrong choice or a lacking of an import parameter may provide undesirable outputs. These parameters were applied on the Bellman-Zadeh algorithm and the membership fuzzy functions, in order to find the appropriate DG site inside a distribution system model. These two methods are described separately. However, the methods are applied on a practical example together. Therefore it is possible to analyze the main characteristics of each method, emphasizing its applications on the multi-objective analysis. The developed methodology intends to provide positive effects in distribution networks and also work towards the planning of distribution systems. It is important to observe that the methodology presented in this study may be applied to distribution system feeders to find in which feeder will be the most appropriate DG location, and to any node inside a determined feeder providing a specific place for the appropriate DG site.